Synthesis and characterization of pyrrolylated-chalcones as anti methicillin-resistant Staphylococcus aureus agents - Gunasekharan, Mohanapriya (2020)
A bacterial infection is well recognized as one of the leading causes of fatal morbidity and death in patients infected with diseases, hence are immune compromised. Although some molecules including vancomycin and linezolid, the standard drugs used for the treatment of methicillin-resistant Staphylococcus aureus (MRSA), have been successfully developed over the years, the ability of microorganisms to develop resistance to these drugs during treatments has evoked the need for a continuous search for new drugs with better efficacies. Chalcone has been one of the most studied class of molecules possessing variety of remarkable bioactivities, including anti-bacterial, anti-parasitic and anti-inflammatory. Due to the ease of preparation and numerous pharmacological activities involving the chalcone motifs, therefore, it is worth to further study the anti-bacteria activity, specifically related to the multidrug-resistant methicillin-resistant Staphylococcus aureus (MDR-MRSA) on the new analogs of the pyrrolylated-chalcones. In this study, a series of pyrrolylated-chalcone analogs (compounds 1-15) were synthesized by treating 2-acetylpyrrole with respectively substituted benzaldehydes via a base-catalyzed Claisen-Schmidt condensation reaction. The purified final compounds were subjected for confirmatory structural elucidation by established spectroscopic techniques comprising of 1H, 19F- and 13C- high field nuclear magnetic resonance (NMR), direct injection-mass spectroscopy (DI-MS), and Fourier transform infrared (FTIR) spectroscopy. The purified pyrrolylated-chalcones were then assayed for anti-MRSA activity through the disk diffusion (DDA, for a preliminary screening), in vitro minimal inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and killing time curve assays. Based on the results, the hydroxyl-containing compounds (8, 9, and 10) showed the most significant anti-MRSA property, with range of inhibition zone diameters between 7.5 to 10 mm and the MIC and MBC values ranged of 0.08 to 0.70 mg/ml and 0.16 to 1.88 mg/ml, respectively. In comparison, the inhibition zone for the standard drug, chlorhexidine (CHX) was 14 to 15 mm in diameter with a respective MIC and MBC values of 0.03 to 0.12 mg/ml and 0.07 to 0.23 mg/ml. The time-kill curve plots showed that MRSA strains to a concentration of 4× MIC for four hours resulted in the death of all cells. Furthermore, ligand 9 was chosen for docking analyses with penicillin-binding protein 2a (PBP2a, PDB ID: 6Q9N) and the results showed a similar bonding interaction to the specific docking of the CHX with the respective binding affinity scores of -7.0 kcal/ mol and -8.2 kcal/mol. Following that, the morphology of compound 9 was further confirmed by the scanning electron microscopy (SEM) technique. Overall results suggested that the pyrrolylated-chalcones, particularly compound 9 may be considered as potential inhibitor in the design of new anti-MRSA agents.